2019
DOI: 10.3389/fpsyt.2019.00649
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Antipsychotic Dosage Change in the First Year of Treatment in Schizophrenia Spectrum and Bipolar Disorders

Abstract: Background: Use of antipsychotic medication is central in the treatment of psychotic disorders. However, there is limited knowledge about prescription practice of antipsychotics in the critical early phase of these disorders. Clinical guidelines recommend low dosages, but no discontinuation of antipsychotic medication during the first year of treatment in first episode patients. The main aim of this study was to identify clinical predictors for dosage change or discontinuation of antipsychotics during this per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Of note, in this analysis a slightly higher proportion of younger than older patients experienced weight increase (10.7% and 7.2%) while in the current study the difference was limited (6.6% versus 7.2%). 48 PP3M generally exhibited a favourable safety profile and was well tolerated in both age and duration groups. The proportion of patients with possible/probable or very likely drug-related TEAEs was slightly higher in the younger versus the older group and was also higher in the shorter versus longer duration group.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Of note, in this analysis a slightly higher proportion of younger than older patients experienced weight increase (10.7% and 7.2%) while in the current study the difference was limited (6.6% versus 7.2%). 48 PP3M generally exhibited a favourable safety profile and was well tolerated in both age and duration groups. The proportion of patients with possible/probable or very likely drug-related TEAEs was slightly higher in the younger versus the older group and was also higher in the shorter versus longer duration group.…”
Section: Discussionmentioning
confidence: 94%
“…Of note, in this analysis a slightly higher proportion of younger than older patients experienced weight increase (10.7% and 7.2%) while in the current study the difference was limited (6.6% versus 7.2%). 48 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, SGAs are considered the mainstay of treatment for both acute episodes’ management and relapse prevention of schizophrenia. 4 Moreover, they are increasingly used in different phases of BD. 5 Clinical evidence has shown that cariprazine could be especially favorable for patients with predominant negative symptoms with an excellent tolerability profile.…”
Section: Introductionmentioning
confidence: 99%
“…Although the predictors of antipsychotic LAI discontinuation were not studied extensively, different factors including the number of hospitalizations before treatment, the setting where the treatment was started, dose of LAI antipsychotic, history of combined antipsychotic treatment, substance abuse and duration of illness were found to be related to treatment discontinuation [37,52] Similarly, we showed that the type of prescribed antipsychotic LAI at baseline together with a history of multiple substance use disorders may favor treatment discontinuation during the 12-month follow-up period. In this regard, some authors reported that early non-response to an antipsychotic is associated with long-term discontinuation of this antipsychotic [53]. For instance, a RCT study found that early response to olanzapine LAI predicts long-term clinical stabilization, similarly to what happens with oral antipsychotics [54].…”
Section: Discussionmentioning
confidence: 99%